MENAKAR PRO-KONTRA HUKUM UJRAH PENGAJAR ILMU AGAMA DAN URGENSINYA DALAM KONTEKS ERA MODERN - Samheri S.HI M.Sh (STIU Al-Mujtama Pamekasan, 2019)
Abstract: This research is based on the legal controversy of wages for Islamic religious teachers that occur in society which is often used as a reason for people to ridicule one another with reasons for preaching and or teaching Islam not sincerely and materialistically. Even though people who are mocked also have legitimate reasons and arguments in doing their dakwah and teaching by taking wages from their dakwah or teaching. This research is librabry research which focus on the written data with research focus is how important wages for islamic religious teachers and its consequences in daily life, then how about the legal law in recieving a wage for islamic religous teachers. The result of this research is giving a wages is mandatory if islamic teacher’s job is just as a Islamic religious teacher (no job else). Beacause of teaching the religous subject is an obligation for all of people who knows about religous knowladge. Islamic law scholars’ opinions are different about this issue. According to one of them giving wages is legal, and others stated illegal, but however giving wages for the Islamic teachers is reasonable or permitted. Because all this time there is no complain from the society to give wages for Islamic religious teachers. Keyword: Legal, Controvercy, Wages (Ujrah), Urgency, Islamic Religious Teachers.